The Effect of Using HOTS-Based Student Worksheets on Student Learning Outcomes and Activities at MA Mannilingi Bulo-Bulo Jeneponto - A. Fitriani Suryadi; Lutfi Lutfi; Akhmad Kurnia; Muhammad Wajdi (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2025)
This study aims to determine the effect of using HETS-based Student Worksheets (LKS) on student learning outcomes and activities. This study used a quasi-experimental design with a non-equivalent control group and involved 60 students from two classes at Madrasah Aliyah Mannilingi, Jeneponto. The experimental group was given HOTS-based LKPD, while the control group used conventional LKPD. Data were collected through pre-test and post-test assessments, student activity observation sheets, and student response questionnaires. The results showed that the experimental group experienced a significant increase in learning outcomes with an average score of 69.63 for the control class and 90.60 for the experimental class. In addition, student activity in the experimental group was higher with an average score of 4.2 (very active), while the control group obtained a score of 2.8 (quite active). The N-Gain value for the experimental group was 0.72 (high category), indicating a substantial increase in " ". The independent t-test showed a highly significant difference between the two groups of the importance of implementing HOTS-based LKPD in the learning process, which can help improve students' higher-order thinking skills and problem-solving abilities. This study provides a significant contribution to educators and curriculum developers, by showing that implementing a HOTS-based approach in learning materials not only improves learning outcomes, but also prepares students to face real-world challenges. Therefore, it is important for educators and curriculum developers to consider integrating HOTS-based LKPD in their learning designs to achieve better academic outcomes and more optimal critical skill development.